2014
DOI: 10.1007/s11060-014-1598-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of recurrent primitive neuroectodermal tumors (PNET) in children and adolescents with high-dose chemotherapy (HDC) and stem cell support: results of the HITREZ 97 multicentre trial

Abstract: Early studies with high-dose chemotherapy for treatment of relapsed cerebral PNET had shown modest efficacy but considerable toxicity. The HIT97 national trial tested a nonrandomized but stratified relapse protocol using either intensive chemotherapy, potentially high dose, or oral chemotherapy. 72 patients (59 disseminated) whose primary treatment had been surgery (97 %), radiotherapy (88 %), and/or chemotherapy (95 %) were enrolled in the intensive chemotherapy arm at diagnosis of relapse or resistance. As a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 25 publications
4
15
0
Order By: Relevance
“…The poor outcome after MB relapse for patients previously treated with radiotherapy is in line with other reports [ 3 , 4 , 11 , 14 , 15 ]. With regard to the use of HDSCR, there was hope that this approach would be of significant benefit in relapsed malignant brain tumours, and single institution reports showed encouraging results [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…The poor outcome after MB relapse for patients previously treated with radiotherapy is in line with other reports [ 3 , 4 , 11 , 14 , 15 ]. With regard to the use of HDSCR, there was hope that this approach would be of significant benefit in relapsed malignant brain tumours, and single institution reports showed encouraging results [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…Transcellular transport is activated, with formation and movement of vesicles from luminal to abluminal surfaces (6). Vesicles can also merge and form large fenestrations and then form transendothelial channels (7). Drugs (8) can cross the BBB through these intercellular and transcellular ways, and thus be delivered to the brain parenchyma.…”
Section: Clinical Translation Of Us-induced Bbbdmentioning
confidence: 99%
“…drugs. 7 Intraarterial chemotherapy injection consists of locoregional delivery of the drug via the cerebral arteries; a systematic review and meta-analysis has shown that this invasive approach is not superior to intravenous chemotherapy in terms of efficacy and OS. 12 Osmotic disruption of the BBB is performed using hypertonic agents, such as mannitol, injected into a cerebral artery.…”
mentioning
confidence: 99%
“…The study population includes infants, children, adolescents, and young adults (up to and including age 21 years to capture different definitions) with diagnoses of progressive, treatment-refractory, or recurrent MB at the time of study recruitment or following initial treatment [20]. To reflect the earlier classification of MB as an infratentorial small round blue cell tumor, articles on recurrent MB, posterior fossa tumors, primitive neuroectodermal tumors (PNETs), and CNS sarcomas will be included during title and abstract screening [22]. Studies that aggregate children and young adults or children with different types of solid or CNS tumors will be included, provided that participant data and outcomes can be evaluated separately for each group.…”
Section: Populationmentioning
confidence: 99%